Identification of hepatic nuclear factor 1 binding sites in the 5′ flanking region of the human phenylalanine hydroxylase gene: Implication of a dual function of phenylalanine hydroxylase stimulator in the phenylalanine hydroxylation system - Lei, Xiang-Dong (National Academy of Sciences, 1998)
Phenylalanine hydroxylase stimulator (PHS) is a component of the phenylalanine hydroxylation system that is involved in the regeneration of the cofactor tetrahydrobiopterin. It is also identical to the dimerization cofactor of hepatocyte nuclear factor 1 (HNF1) (DCoH) that is able to enhance the transcriptional activity of HNF1. Moreover, it has the structural potential for binding macromolecules such as proteins and nucleic acids, consistent with its involvement in gene expression. We investigated whether PHS/DCoH could enhance the expression of phenylalanine hydroxylase (PAH). Cotransfection assays showed that DCoH itself could not transactivate the 9-kb human PAH 5′ flanking fragment. However, this 9-kb fragment was transactivated by HNF1 in a dose-dependent manner with a maximum of nearly 8-fold activation; DCoH potentiated this transactivation by another 1.6-fold. The HNF1 binding sites were located at −3.5 kb in a region that is 77.5% identical to the mouse liver-specific hormone-inducible PAH gene enhancer. This study suggests a possible dual function of PHS in vivo in the human phenylalanine hydroxylation system: it is involved in the regeneration of the cofactor tetrahydrobiopterin and can also enhance the expression of the human PAH gene.